Effects of human capital on foreign direct investment inflows - Karimi, Mohammad Sharif; Yusop, Zulkornain; Law, Siong Hook; Lee, Chin (Hanyang Economic Research Institute, 2013)
The purpose of this study is to assess whether and to what extent HC contributes to national economies, and the influence it has on subsequent FDI owing into those economies. A systematic empirical study based on the Generalized Method of Moments (GMM) for 50 developed and developing countries has been undertaken by this study; in order to evaluate the role of HC on FDI inflows using all indicators previously used as a HC proxy in previous studies. We have utilized a newly developed index that is focused on weighted HC stock to examine the effects of HC on FDI inflows. The results clearly indicate that HC is important for attracting FDI in developing and developed countries. It demonstrates that the general educational attainment of a country is of importance in the FDI context. It would appear that HC formation should be emphasized in developing countries if FDI attraction is to be considered as a valid policy objective.